Global Warming - Om Books International (Bharat Om Books International, 2021)
Mother Earth is in deep danger. The changes in Global climate patterns are to blame. Why is this happening? Jonathan, Tina and their parents explore how they can contribute towards making this world a clean and healthy place to live in. This vividly illustrated, brilliantly written story draws attention towards climate change and its impact on our day to-day lives.
Keywords: Read Aloud Section - K -- Read Aloud Section - K